Liquidity Ratio Analysis, Activities and Leverage in Oil and Gas Mining Sub-Sector Companies Listed on the Indonesia Stock Exchange - susanti, aprilia; Nurulrahmatiah, Nafisah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study aims to describe or describe the performance of oil and gas mining sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period based on the Quick ratio, Total asset turnover and Debt to asset ratio. The population in this study are all oil and gas mining sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. Based on the sampling technique used, namely purposive sampling, 3 companies were selected as research samples. The data analysis technique used descriptive analysis of Quick ratio, Total asset turnover and Debt to asset ratio, as well as the t-one sample test which was carried out in SPSS version 22 software. The results showed that the performance of the oil and gas mining sub-sector companies listed on the Indonesia Stock Exchange in bad condition based on Quick ratio, Total asset turnover and Debt to asset ratio.